Postbiotic Metabolite of Lactiplantibacillus plantarum PD18 against Periodontal Pathogens and Their Virulence Markers in Biofilm Formation - Widawal Butrungrod; Chaiyavat Chaiyasut; Netnapa Makhamrueang; Sartjin Peerajan; Wantida Chaiyana; Sasithorn Sirilun (MDPI AG, 2023)
Alternative methods to reduce infectious diseases caused by bacterial pathogens and their virulence factors, biofilm formations, have arisen to reduce the pressure on existing or currently developed disinfectants and antimicrobial agents. The current strategies for reducing the severity of periodontal pathogen-caused disease by using beneficial bacteria and their metabolites are highly desirable. Probiotic strains of lactobacilli related to foods from Thai-fermented foods were selected and their postbiotic metabolites (PM) were isolated with inhibitory activity on periodontal pathogens and their biofilm formation. The PM from Lactiplantibacillus plantarum PD18 (PD18 PM) with the highest antagonistic effect against Streptococcus mutans, Porphyromonas gingivalis, Tannerella forsythia and Prevotella loescheii was selected from 139 Lactobacillus isolates. The minimal inhibitory concentration (MIC) and minimum biofilm inhibitory concentration (MBIC) values of PD18 PM against the pathogens ranged from 1:2 to 1:4. The PD18 PM demonstrated the ability to prevent the biofilm formation of S. mutans and P. gingivalis by showing a significant reduction in viable cells, high percentages of biofilm inhibition at 92.95 and 89.68%, and the highest effective contact times at 5 and 0.5 min, respectively. L. plantarum PD18 PM showed potential as a promising natural adjunctive agent to inhibit periodontal pathogens and their biofilms.